The Influence of Ecological Identity on the Cultural Significance of Traditional Urban Public Spaces in Cultural Landscapes - Ashfina Thurkey; Rokhsaneh Rahbarianyazd (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Traditional urban public spaces are highly significant because they retain identities, histories, and memories of the community in any cultural landscape. These spaces have existed since the prehistoric era and are an important part of a landscape's unique identity. These spaces are also a part of larger ecological settings, where ecological features have an impact on the design, purpose, and cultural significance. Therefore, This paper identifies specific indicators of ecological identity through the application of case study analysis and multidisciplinary research methods and explores the influence of ecological features in and around traditional public spaces on their cultural significance within a cultural landscape. The findings reveal that the natural environment and traditional public spaces are intricately entwined with human culture in the chosen study area and emphasise how important it is to comprehend the interactions between ecological and cultural factors to conserve such spaces while promoting sustainable urban development.